Uso da zona ripária como fator determinante da estrutura de uma assembleia de lagartos em área de terra-firme na Amazônia Central - Oliveira, Ayra Souza Faria de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
The factors determining assemblage structure act at different scales, with heterogeneity dominant at the local scale. In Amazonia, such heterogeneity is represented by the different forest types of the region, which provide a great diversity of shelter and food for animal species. Recent changes in Brazilian environmental legislation have put at risk the maintenance of habitat heterogeneity by favoring the suppression of several types of vegetation, notably those in riparian zones. Several Amazonian animal groups have close ecological ties to the presence of water bodies and the environmental gradients provided by them. To understand ecological relationships between species and their environment, model organisms such as lizards are widely used because they are sensitive to environmental changes and because of their success in occupying different habitat types. In this study, an assemblage of lizard species was characterized in terms of distribution and association using biological variables relevant to the group. Twenty species distributed in 10 families were studied. At the scale used in this study, multiple regression models did not indicate a significant effect of environmental variables. However, the riparian zone exerted a strong influence on the species composition and piecewise regression estimated its use to be some 211 m. Several species occurred only in the riparian zone. Our results demonstrate that the current environmental legislation in the country is not adequate to cover the observed variation in habitat use by Amazonian lizards.
Keywords: Ecologia de comunidades; Squamata; Conservação de lagartos